Smart antennas in software radio base stations. - Perez-Neira, A. (IEEE Communications magazine)
The application of adaptive antenna techniques to fixed-architecture base stations has been shown to offer wide-ranging benefits, including interference rejection capabilities or increased coverage and spectral efficiency. Unfortunately, the actual implementation of these techniques to mobile communication scenarios has traditionally been set back by two fundamental reasons. On one hand, the lack of flexibility of current transceiver architectures does not allow for the introduction of advanced add-on functionalities. On the other hand, the often oversimplified models for the spatiotemporal characteristics of the radio communications channel generally give rise to performance predictions that are, in practice, too optimistic. The advent of software radio architectures represents a big step toward the introduction of advanced receive/transmit capabilities. Thanks to their inherent flexibility and robustness, software radio architectures are the appropriate enabling technology for the implementation of array processing techniques. Moreover, given the exponential progression of communication standards in coexistence and their constant evolution, software reconfigurability will probably soon become the only cost-efficient alternative for the transceiver upgrade. This article analyzes the requirements for the introduction of software radio techniques and array processing architectures in multistandard scenarios. It basically summarizes the conclusions and results obtained within the ACTS project SUNBEAM, proposing algorithms and analyzing the feasibility of implementation of innovative and software-reconfigurable array processing architectures in multistandard settings